the PENGARUH KECEPATAN PENGIRIMAN BARANG DAN PENETAPAN HARGA TERHADAP PENINGKATAN PENGGUNAAN JASA PENGIRIMAN PT TRI ADI BERSAMA (ANTERAJA) PADA MASA PANDEMI COVID-19 - Sonya (Jurnal Pendidikan Nusantara, 2022)
The outbreak of the Covid-19 virus since the beginning of 2020 has forced many business arrangements to rack their brains to change direction and innovate. One of the affected business sectors is online sales. This happens because of restrictions on access for purchasing goods offline by the government. This restriction also has an impact on increasing the use of freight forwarding services, one of which is from PT Tri Adi Bersama (Anteraja). The purpose of this research is to know and analyze the impact of goods delivery speed and consumer’s purchasing power to the increased use of delivery services PT Tri Adi Bersama (Anteraja) in Pandemic Covid-19 with quantitative type of research. The data compiled from primer data from the questionnaire spreads to 150 consumers of Anteraja in Jabodetabek area from May until July 2021. The result of this research is the variable of goods delivery speed and consumer’s purchasing power have positive and significant impact to the increased use of delivery services PT Tri Adi Bersama (Anteraja) in Pandemic Covid-19.